2018
DOI: 10.1016/j.biopsycho.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the neurodynamics of insight: A meta-analysis of neuroimaging studies

Abstract: The nature of insight has been the interdisciplinary focus of scientific inquiry for over 100 years. Behavioral studies and biographical data suggest that insight, as a form of creative cognition, consists of at least four separate but intercorrelated stages as described by Wallas (1926). Yet no quantitative evidence was available for insight- or insight-stage-specific brain mechanisms that generalize across various insight tasks. The present work attempted, for one, to present an integrated and comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 98 publications
0
58
0
1
Order By: Relevance
“…There has been substantial research in the last decade investigating the neural basis for solutions accompanied with an AHA! in insight problems (see Shen, 2018 for a meta-analysis). Increased activations in the medial temporal lobe (amygdala, hippocampus, and parahippocampal gyrus) (Jung-Beeman et al, 2004;Kizilirmak, Thuerich, Folta-Schoofs, Schott, & Richardson-Klavehn, 2016;Ludmer, Dudai, & Rubin, 2011;Zhao et al, 2013) and right anterior superior temporal gyrus (Jung-Beeman et al, 2004;Tik et al, 2018) amongst other areas have been reported in solutions with compared to without AHA!…”
Section: Neural Basis For the Aha! Experiencementioning
confidence: 99%
“…There has been substantial research in the last decade investigating the neural basis for solutions accompanied with an AHA! in insight problems (see Shen, 2018 for a meta-analysis). Increased activations in the medial temporal lobe (amygdala, hippocampus, and parahippocampal gyrus) (Jung-Beeman et al, 2004;Kizilirmak, Thuerich, Folta-Schoofs, Schott, & Richardson-Klavehn, 2016;Ludmer, Dudai, & Rubin, 2011;Zhao et al, 2013) and right anterior superior temporal gyrus (Jung-Beeman et al, 2004;Tik et al, 2018) amongst other areas have been reported in solutions with compared to without AHA!…”
Section: Neural Basis For the Aha! Experiencementioning
confidence: 99%
“…And there were mainly four insight-activated brain regions, including the right medial frontal gyrus, the left inferior frontal gyrus, the left amygdala, and the right hippocampus. Importantly, various brain regions were variably activated during the four stages, and the gesture might lead to activation of one brain region and then help improved performance Shen et al (2018a) . However, the exact activated brain region was still not clear in the process of embodied action facilitating insight problem solving, and it should be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…The putamen has generally been associated with behavioural inhibition (Sweitzer et al, 2018;Thames et al, 2012). In a recent metaanalysis Shen et al (2018) found the bilateral putamina to be associated with spontaneous insight solutions. The putamen was, furthermore, found to have a high density of D2 receptors (Willeit et al, 2016).…”
Section: /32mentioning
confidence: 99%
“…Boot et al (2017) suggest moderate dopamine release in the striatum to be beneficial for flexibility in cognition, perspective switching and the broadening of the attentional focus. Furthermore, the putamina are involved in spontaneous insights (Shen et al, 2018). The putamen is moreover associated with behavioural inhibition (Sweitzer et al, 2018;Thames et al, 2012).…”
Section: /32mentioning
confidence: 99%